Ocular morbidity among porters at high altitudes - Gnyawali, Subodh; Shrestha, Gauri Shankar; Khanal, Safal; Dennis, Talisa; Spencer, John C (Nepalese Journal of Ophthalmology, 2017)
Introduction: High altitude, often characterized by settings over 2400m, can be detrimental to the human body and pose a significant risk to ocular health. Reports concerning various ocular morbidities occurring as a consequence of high altitude are limited in the current literature. Objectives: This study was aimed at evaluating the ocular health of porters working at high altitudesof Himalayas in Nepal. Materials and methods: A mobile eye clinic was set up in Ghat and patient data were collected from its out- patient unit by a team of seven optometrists which was run for five days. Ghat is a small village in north-eastern Nepal, located at 2860 m altitude. Travellers walking through the trekking route were invited to get their eyes checked at the clinic. Comprehensive ocular examinations were performed, including visual acuities, objective and subjective refraction, anterior and posterior segment evaluations, and intraocular pressure measurements; blood pressure and blood glucose levels were also measured as required. Ocular therapeutics, prescription glasses, sunglasses and ocular health referrals were provided free of cost as necessary. A total of 1890 people visited the eye clinic, among which 57.4% (n=1084) were porters. Conclusions: Almost half of the porters had an ocular morbidity. Correctable refractive error was most prevalent, with other ocular health-related complications, including dry eye disease, infectious disorders, glaucoma and cataract. Proper provision of regular and effective eye care services should be made more available for those residing at these high altitudes in Nepal.